GLP-1 Based Therapies: Potential for Drug - Disease Interaction - Vinall, Maria (MD Conference Express, 2013)
This article discusses potential drug/disease interaction between the glucagon-like peptide-1 (GLP-1)-based diabetic therapies and pancreatitis (acute and chronic) and pancreatic cancer.